Pitfalls of laparoscopic Re-TAPP in recurrent inguinal hernia repair—a plea for extended preoperative diagnostic. Issue 3 (29th March 2021) - Raguz, Ivana; Burger, Reint; Vonlanthen, Rene; Bueter, Marco; Thalheimer, Andreas
Abstract: According to international guidelines, recurrent inguinal hernia should be treated by a surgical approach opposing of the primary strategy (anterior–posterior or posterior–anterior). However, recent evidence demonstrates feasibility and safety of re-laparoscopic repair of recurrent inguinal hernia after primary laparoscopy. For such a strategy, correct identification of anatomical structures is challenging, but absolutely crucial for a satisfactory postoperative result. This case of an unrecognized sliding hernia of the sigmoid colon during re-laparoscopy highlights that a precise physical examination as well as an extended preoperative radiological workup (ultrasound, computed tomography and/or magnetic resonance imaging of the abdomen and pelvis) should be considered prior to re-laparoscopy of recurrent inguinal hernia.